Association between daily variations in the levels of atmospheric O3, PM2.5, and NO2 and the frequency of hospital visits due to respiratory diseases and hypertension in Mexico City using Generalized Additive Mixed Models - Vega, Elizabeth; Ruiz-Olivares, Alejandro; Miquelajauregui, Yosune; Rentería-Campos, Regina; Bramwell, Lindsay; Feytmans, Romain Bernard M.; Namdeo, Anil; Núñez-Enríquez, Juan Carlos; Entwistle, Jane A.; Jaimes-Palomera, Mónica; Torres-Rojas, Nancy Minerva; Rascón-Pacheco, R. Alberto; et al. (Frontiers in Public Health, 2025)
BackgroundEnvironmental pollution is a significant public health issue in Mexico City. Patients with respiratory or cardiovascular diseases such as asthma or hypertension often experience exacerbations triggered by environmental factors. This retrospective time series epidemiological study analyzed the association between daily air pollution levels and the numbers of medical visits for exacerbations of cardiorespiratory diseases.MethodsRecords from primary, secondary, and tertiary hospitals of the Mexican Institute of Social Security (IMSS) were reviewed between 2017 and 2019. Air quality data, including PM2.5, PM10, O3, and NO2 concentrations were collected hourly from air quality monitoring stations at fixed sites. To fit the models andtake into account temporal autocorrelation and the complex non-linear relationships between pollutants and cardiorespiratory diseases, Generalized Additive Mixed Models (GAMM) were applied.ResultsPM2.5, O3, and NO2 exposure showed a strong association with an increase in visits for upper respiratory diseases. Age was a relevant factor: individuals aged between 19–35 years were the most affected, whereas those aged 66–100 years were least affected. An effect on the weekdays was identified, with peaks in visits on Mondays and decreases on Saturdays. Also, seasonally, results showed an increase in October and declines in August. Regarding hypertensive diseases, only PM2.5 exhibited an association. The models confirmed the link between air pollution levels and respiratory disease exacerbations, highlighting key public health implications.ConclusionThis study provides strong evidence that short term exposure to elevated concentrations of atmospheric pollutants, specifically PM2.5, O3, and NO2, are significantly associated with an increase in medical visits for upper respiratory diseases, asthma, and hypertension in Mexico City. By employing Generalized Additive Mixed Models and analyzing health records from IMSS-affiliated hospitals between 2017 and 2019, we observed that the effects of air pollution varied by disease, age group, season, and day of the week.